Cysteine as a Carbon Source, a Hot Spot in Cancer Cells Survival - Serpa, Jacinta (Frontiers in Oncology, 2020)
Cancer cells undergo a metabolic rewiring in order to fulfil the energy and biomass requirements. Cysteine is a pivotal organic compound that contributes for cancer metabolic remodeling at three different levels: 1) in redox control, free or as a component of glutathione; 2) in ATP production, via hydrogen sulfide (H2S) production, serving as a donor to electron transport chain (ETC), and 3) as a carbon source for biomass and energy production. In the present review, emphasis will be given to the role of cysteine as a carbon source, focusing on the metabolic reliance on cysteine, benefiting the metabolic fitness and survival of cancer cells. Therefore, the interplay between cysteine metabolism and other metabolic pathways, as well as the regulation of cysteine metabolism related enzymes and transporters, will be also addressed. Finally, the usefulness of cysteine metabolic route as a target in cancer treatment will be highlighted.